Advanced multipath modeling and validation for GPS onboard the International Space Station. Issue 3 (25th July 2019) - Klein, Viliam; Axelrad, Penina
Abstract: Experiments conducted onboard the International Space Station (ISS) that rely on GPS for positioning and timing must take into account potential performance degradation caused by the complex multipath environment around the station. The Advanced GNSS Multipath Model (AGMM) has been developed to simulate the station structure, dynamics, and receiver characteristics necessary for accurate multipath analysis. Results from case studies at the planned location of the Global Ecosystem Dynamics Investigation Lidar (GEDI) mission show code and carrier multipath error magnitudes of at least 1.5 m and 1.4 cm. Model validation was attempted by comparison to a short segment of on‐orbit data gathered from the SIGI receiver. The simulation produced realistic code and carrier multipath for some satellite passes. However, low elevation passes along the truss line of sight were not well matched due to structures on the ISS that were not included in the AGMM ISS CAD model.